Health education as a tool in the prevention of parasitosis - Maria de Fátima Antero Sousa Machado; Ayslane Patrícia Nascimento de Macedo; Ana Luisa Almeida Melo; Loeste de Arruda Barbosa; Ana Léa Alcântara Sampaio (Universidade de Fortaleza, 2009)
Objective: To aware children and their parents on the prevention of parasitic diseases in childhood by means of Health Education actions. Methods: A descriptive study of educational intervention with residents of a neighborhood in the municipality of Crato - CE, in partnership with the Family Health strategy. Fecal samples from children aged 2 to 8 years were collected for analysis by both direct and Holffmann methods and from the results, we directed the educational process for children and their parents on preventive behaviors for infection by intestinal parasites. Results: Regarding to material collection and the analysis of the results, approximately 47% of the containers for collection of feces were delivered, comprising 21 samples and, from this total, 10 children had some type of parasites, the most frequent being: Giardia lamblia, Entamoeba histolytic, Entamoeba coli, Endomilax nana and Ascaris lumbricoides. The educational moment occurred with the participation of 48 persons, among them 16 children. There was medical consultation and prescription of antiparasitic drugs to children, with positive results for some type of parasites. Both children and their parents showed to have understood the message by actively participating in educational activities. Conclusion: The population proved to be aware of the actions taken, and succeeded the educational process carried out in a subject-subject approach and not in a vertical manner, in the search for community empowerment on the issues raised, stressing the importance of a continuous process of health education.